Fabrication and Photovoltaic Characteristics of Coaxial Silicon Nanowire Solar Cells Prepared by Wet Chemical Etching - Chien-Wei Liu; Chin-Lung Cheng; Bau-Tong Dai; Chi-Han Yang; Jun-Yuan Wang (International Journal of Photoenergy)
Nanostructured solar cells with coaxial p-n junction structures have strong potential to enhance the performances of the silicon-based solar cells. This study demonstrates a radial junction silicon nanowire (RJSNW) solar cell that was fabricated simply and at low cost using wet chemical etching. Experimental results reveal that the reflectance of the silicon nanowires (SNWs) declines as their length increases. The excellent light trapping was mainly associated with high aspect ratio of the SNW arrays. A conversion efficiency of ∼7.1% and an external quantum efficiency of ∼64.6% at 700 nm were demonstrated. Control of etching time and diffusion conditions holds great promise for the development of future RJSNW solar cells. Improving the electrode/RJSNW contact will promote the collection of carries in coaxial core-shell SNW array solar cells.